Structural, optical, and radiation shielding features for a series of borate glassy system modified by molybdenum oxide - Alajerami, Y. S. M.; Morsy, Mohamed A.; Mhareb, M. H. A.; Sayyed, M. I.; Imheidat, Mohammad A.; Hamad, M. Kh; Karim, M. K. A. (Springer, 2021)
This work aims to explore the radiation shielding and structural features for a new glass composition 10SrO–20CdO–xMoO3–(70 − x) B2O3 where 0 ˂ x < 20 mol% that fabricated via conventional melt-quench method. The amorphous behavior for vitreous samples was obtained by X-ray diffraction (XRD), while the vibration for functional group BO3 and BO4 was achieved by Fourier transform infrared (FTIR). FTIR results appear the transformation from BO4 to BO3 with the addition of MoO3. Moreover, several optical and physical features were defined for evaluation of the glass structure. On the other hands, the gamma and neutron shielding parameters were defined by utilizing the Phy-X program. The impact of MoO3 is evident on the neutron and gamma shielding properties. The fast neutron removal cross-section (ΣR) and mass attenuation coefficient (MAC) showed a progressive enhancement with adding the MoO3 instead of B2O3. In conclusion, adding the MoO3 to the glass system enhanced the neutron and gamma shielding features, so it is recommended to use this glass system as a radiation shielding substance.